Development of GM2015 Computational Fluid Dynamics (CFD) Methodology for Naturally-ventilated Non-residential Buildings (NRB) in Singapore. (February 2019) - Poh, Hee Joo; Chiu, Pao-Hsiung; Ooi, Chin Chun; Raghavan, Venugopalan; Wan, Stephen; Xu, George; Li, Ruixin; Ming, Leong-Kok Su
Abstract: This paper aims to share about the recent development on the performance-driven and scientific-based CFD quality control and framework in order to assess the naturally ventilated building designs in Singapore. The topic is an essential component for Green Mark 2015 Schemes, recently advocated by Building & Construction Authority (BCA), Singapore, for the sake of green and sustainable building designs. It covers six (6) different types of NRB buildings, namely with regard to industrial facilities, healthcare facilities, commercial atriums, hawker centres, sports facilities, and schools. A comprehensive quality control checklist is also developed to ensure the quality and accuracy of the simulation results. In addition to the regulations from respective building stakeholders, the adopted parameters also take reference from internationally accepted standards and/or peer reviewed literatures. This CFD methodology development can help to supplement limited guideline on natural/passive ventilation for the building code of practice in Singapore. Finally, based on the efforts in this project, we will summarize the potential research topics that may require further collaboration with building practitioners, e.g. pilot scale study on certain building type and good modelling approach/tool to support both building designers and policy makers.